2002
DOI: 10.1046/j.1528-1157.2002.34601.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Visual Attention in West Syndrome

Abstract: Summary:Purpose: To study prospectively the evolution of visual attention in children with West syndrome to evaluate its development before the onset of spasms, its possible deterioration as a consequence of epileptic disorders, and its outcome at the age of 2 years, and the possible relation between the impairment of visual attention and cognitive development.Methods: Infants with symptomatic West syndrome were examined before the onset of spasms and until age 24 ± 2 months. Visual attention study (through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 11 publications
(13 reference statements)
5
27
0
2
Order By: Relevance
“…These findings are supported by previous observations that the posterior cortex may be important in the pathogenesis of infantile spasms (Wenzel, 1987, Guzzetta et al, 2002, Metsahonkala et al, 2002, Rando et al, 2005, Siniatchkin et al, 2007, Juhasz et al, 2001. It has been…”
Section: Functional Connectivity In Hypsarrhythmiasupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are supported by previous observations that the posterior cortex may be important in the pathogenesis of infantile spasms (Wenzel, 1987, Guzzetta et al, 2002, Metsahonkala et al, 2002, Rando et al, 2005, Siniatchkin et al, 2007, Juhasz et al, 2001. It has been…”
Section: Functional Connectivity In Hypsarrhythmiasupporting
confidence: 89%
“…shown that the visual abnormalities such as poor visual responsiveness, abnormal visual evoked potentials, and deficits in fixation shift can already be detected at the early stages of West syndrome and even before (Wenzel, 1987, Guzzetta et al, 2002, Rando et al, 2005. Focal posterior cortical hypometabolism has been found in a great proportion of children with the West syndrome (Chugani et al, 1990, Jambaque et al, 1993, Metsahonkala et al, 2002.…”
Section: Functional Connectivity In Hypsarrhythmiamentioning
confidence: 99%
“…West syndrome (infantile spasms): Lack of visual attention manifesting as lack of visual eye movements may precede the onset of epilepsy (Guzzetta et al 2002 ), and it is essential to suspect this diagnosis in all infants who appear not to see from birth.…”
Section: Malformations Of Cortical Development (Brodsky 2010 )mentioning
confidence: 99%
“…Impaired eye-hand coordination was found to be deficient when infants were evaluated, even in idiopathic patients who appear to be functioning normally otherwise (Rando et al 2005). Impaired visual functioning involving acuity, ocular motility, visual field, visual attention, and visual scanning skills have been found in several studies with infants (Guzzetta et al 2002;Rando et al 2004). Guzzetta (2006) reported an associated deficit in auditory attention, and visual and auditory functions were both correlated with cognitive competence on the Griffith Scales of Infant Development.…”
Section: West Syndromementioning
confidence: 93%